Research Progress of Antibiotic Resistance Genes (Args) Pollution in Drinking Water Source. Issue 4 (February 2020) - Dong, Xiaotong; Sun, Shaohua; Xu, Lirong; Hou, Wei; Wang, Mingquan; Zhao, Qinghua; Ji, Guangxue; Jia, Ruibao
Abstract: In recent years, the problem of the pollution of antibiotic resistance genes(ARGs)in water environment is becoming more and more serious. As a new environmental pollutant, people have been paid more attention to the harmfulness of ARGs in drinking water sources. The source of ARGs, pollution status, detection and identification technology and water treatment technology have been systematically reviewed, and the future research directions of ARGs were prospected.